A Kontrol Diri dengan Motivasi Belajar SMA Negeri 1 - Shanam Al Dhuha; Octa Reni Setiawati; Sri Maria Puji Lestari; Prambudi Rukmono (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
the ability to guide their own behavior, the ability to suppress or inhibit impulses or impulsive behavior is a sense of self-control. a significant role in the effort to learn the definition of motivation. Because students are not possible without the motivation of learning activities. Learning is a complex process that happens to every person throughout his life. Between the self-control with student achievement there is a significant positive relationship. Thus, self-control is a control behavior that tends to act positively in thinking. Knowing the self-control relationship with the motivation to learn at SMA Negeri 1 Trimurjo Central Lampung. Research quantitative analytic design and cross-sectional design and sampling techniques Simple Random Sampling by questionnaire self-control and motivation to learn. Total sample 205 Of 500 population, self-control with a mean of 82.80 (medium), ± Std.Deviation (13 792), while the motivation to study with a mean of 80.94 (medium), ± Std.Deviation (13,572) for the motivation to learn. The results of the bivariate analysis values ​​obtained Pearson test P Value 0.003, and the value of r 0.209. There is a significant relationship between self-control and motivation to learn at Senior High School 1 Trimurjo Central District Lampung, with the strength and direction of the correlation was positive correlation that the higher the self control, the higher a person's motivation to learn.